Is there still an economic right to water? An analysis of the intersection of rights and regulatory regimes - Shepheard, M (Foundation for Law, Justice and Society, 2013)
This policy brief addresses how the meaning and scope of farmers’ economic rights to access and use water are changing through increasing emphasis on stewardship responsibilities. It outlines how regulation is increasingly seeking closer alignment of water use and stewardship by injecting public interest considerations into the legal interpretation of water rights. This has the potential to enhance the public accountability of private right holders. Market-based water resource management in England and Wales is currently being considered by the UK government as one option for further promoting water stewardship. The policy brief highlights key issues discussed during a workshop held in Oxford on 19 March 2013 that addressed the question whether it is still meaningful to talk of an economic ‘right’ to water in the context of increasing restrictions on water use in England and Wales. The policy brief concludes with a series of recommendations. An appropriate legal and institutional framework for delivering an integrated catchment approach must be developed in order to align water use with water stewardship. Farmers, as managers of extensive land areas, need to be part of this. Lastly, integrated catchment management needs to entail clear standards of performance for water users in order to align water use with water stewardship.